Reducing antibiotic duration for acute otitis media: clinician, administrator, and parental insights to inform implementation of system-level interventions - Deborah J. Rinehart; Aiden Gilbert; Sonja O’Leary; Sophie E. Katz; Holly M. Frost (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract